A Steiner Zone Approach for Mobile Data Collection in Partitioned Wireless Sensor Networks - Şentürk, İzzet Fatih (My University, 2020)
Wireless sensor networks (WSNs) typically operate in harsh environmental conditions. Hardware constraints and external damage from inhospitable surroundings leave the nodes susceptible to node failures. Depending on the damage scale, the network can be subject to partitioning which segments the network into multiple isolated connected components. A prompt reactive approach to restore network connectivity is to employ a mobile data collector (MDC) that visits and collects data from partitions periodically. Availability of the wireless data communication through multi-hop routing in a partitioned network complicates designating the shortest possible route for data collection. This paper regards the mentioned data collection problem as the Close-enough Traveling Salesman Problem (CETSP) and employs Steiner zone approach to designate respective data collection points for corresponding partitions. We have assessed the proposed approach in terms of the number of points visited for data collection and the total travel distance of the MDC. Obtained results indicate that the proposed approach can reduce the number of data collection points up to 67% and total travel distance up to 42%.

Kablosuz algılayıcı ağlar genellikle zorlu çevresel koşullar altında faaliyetlerini sürdürürler. Donanımsal kısıtlar ve olumsuz kuşatanlar ağı oluşturan düğümleri kayıplara maruz bırakır. Ortaya çıkan hasarın boyutuna bağlı olarak ağ içerisinde, ağın geri kalanından yalıtılmış ayrık bağlı bileşenler ortaya çıkabilir. Bu tür durumlarda ağ bağlantısının hızlı ve tepkin şekilde onarılması için hareketli veri toplayıcılarından (HVT) faydalanılabilir. HVT, parçalanmış ağdaki bağlı bileşenleri belirli aralıklarla ziyaret ederek toplanan verilerin iletilmesine olanak sağlar. Çok-sekmeli yol atamanın mümkün olması, parçalanmış bir ağdan kablosuz veri iletimi ile veri toplayacak maliyet-etkin güzergahın tespiti problemini karmaşıklaştırmaktadır. Bu makale, belirtilen veri toplama problemini Yeterince Yakın Gezgin Satıcı Problemi (YYGSP) olarak ele alarak Steiner zone yaklaşımı ile her bir ağ parçası için ilgili veri toplama noktasını tayin eder. Önerilen yöntemin başarımının değerlendirilmesi için ziyaret edilen veri toplama noktalarının sayısı ve HVT’nin toplam seyahat mesafesi ölçülmüştür. Elde edilen sonuçlar, önerilen yöntemin, veri toplama noktalarının sayısını %67, toplam seyahat mesafesini ise %42 düşürdüğünü göstermektedir.
Steiner Zone Yaklaşımı İle Bölünmüş Kablosuz Algılayıcı Ağlarda Hareketli Veri Toplama
Keywords: [No Keywords]